2015
DOI: 10.1016/j.nmni.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of blaOXA-23 in Acinetobacter spp. and detection of blaNDM-1 in A. soli in Cuba: report from National Surveillance Program (2010–2012)

Abstract: As a first national surveillance of Acinetobacter in Cuba, a total of 500 Acinetobacter spp. isolates recovered from 30 hospitals between 2010 and 2012 were studied. Acinetobacter baumannii–calcoaceticus complex accounted for 96.4% of all the Acinetobacter isolates, while other species were detected at low frequency (A. junii 1.6%, A. lwoffii 1%, A. haemolyticus 0.8%, A. soli 0.2%). Resistance rates of isolates were 34–61% to third-generation cephalosporins, 49–50% to β-lactams/inhibitor combinations, 42–47% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
2
11
1
1
Order By: Relevance
“…We obtained 32 (72.72%) isolates carried bla OXA-23 and 13 (29.54%) isolates carried bla OXA-58. .These results were in agreement with Quiñones et al, (2015) (35) who found that, from 30 A.baumannii strains 76% were positive for bla OXA-23 gene and 3% were positive for bla OXA-58 by multiplex PCR, on the other hand, Shoja et al, (2013) (36) detected bla OXA-23 in 85% of isolates but the bla OXA-58 was not found, resistance to carbapenems in these isolates may be related to other mechanisms including decreased permeability, alteration of penicillin-binding proteins, AmpC stable derepression and overexpression of efflux pump (37) .…”
Section: Test Of Significancesupporting
confidence: 93%
“…We obtained 32 (72.72%) isolates carried bla OXA-23 and 13 (29.54%) isolates carried bla OXA-58. .These results were in agreement with Quiñones et al, (2015) (35) who found that, from 30 A.baumannii strains 76% were positive for bla OXA-23 gene and 3% were positive for bla OXA-58 by multiplex PCR, on the other hand, Shoja et al, (2013) (36) detected bla OXA-23 in 85% of isolates but the bla OXA-58 was not found, resistance to carbapenems in these isolates may be related to other mechanisms including decreased permeability, alteration of penicillin-binding proteins, AmpC stable derepression and overexpression of efflux pump (37) .…”
Section: Test Of Significancesupporting
confidence: 93%
“…In our present study, NDM-1 gene was identified in two ExPEC isolates of phylogenetic group B1-ST448 that were isolated from sporadic infections in 2016, representing NDM-detection rate of 0.7% (2/306). This is the first report of NDM-1 gene in E. coli in Cuba, although we identified bla NDM-1 in a rare Acinetobacter species, A. soli in 2011 [27]. It was also remarkable in the present study that bla NDM-1 was detected in a rare E. coli clone, ST448.…”
Section: Discussionsupporting
confidence: 59%
“…Acinetobacter spp. harboring bla NDM-1 in pNDM-BJ01-like plasmids are frequently detected all over the world ( Feng et al 2015 ; Fu et al 2015 ); these (or NDM-positive isolates with bla NDM-1 genetic surroundings suggesting the presence of pNDM-BJ01-like plasmids) have even been found in Latin America ( Waterman et al 2013 ; Pasteran et al 2014 ; Brovedan et al 2015 ; Quinones et al 2015 ; Montana et al 2016 ; Rojas et al 2016 ). Here, we report an A. baumannii clone isolated in Colombia that also harbors bla NDM-1 in a pNDM-BJ01-like plasmid.…”
Section: Discussionmentioning
confidence: 99%